Against the odds: Foster carers' perceptions of family, commitment and belonging in successful placements. (January 2013) - Oke, Nicholas; Rostill-Brookes, Helen; Larkin, Michael
This study examines carer attributes associated with placement stability for teenagers growing up in long term foster care, focusing on unexpected placement success. We explored experiences and perceptions relating to family, belonging and commitment in a group of foster carers providing a stable placement for a young person who had not been expected to settle. These placements showed positive outcome, despite factors in the child's history that might have predicted otherwise. Seven foster carers were interviewed following a semi-structured guide, which covered their ideas about their relationship with the child in question, about the foster family, and the child's sense of belonging in foster and birth family. Analysis of carers' accounts of placements which had succeeded 'against the odds' revealed four major themes, described under the headings My Child —emotional bonding, the carers' enlarged view of family and their parental regard for the young person; Jam in the Sandwich —working within a 'compromised space' between Local Authority and birth family; Repair and Rebuild —the craft of fostering including managing the foster/birth family boundary; Sticking with It —resilience, tenacity and maintaining hopefulness. The carers' accounts offer pointers towards the ingredients of successful placements and prompt reflection on how these may be supported and promoted. They also highlight tensions inherent in the foster carer task relating to carers' parental functioning for young people in long-term foster care.